ChemInform Abstract: Magnetic Properties and Phase Diagram of NdPd5Al2. Issue 26 (June 2016) - Zubac, Jan; Vlaskova, Kristina; Prokleska, Jan; Proschek, Petr; Javorsky, Pavel
Abstract: Single crystals of the tetragonal intermetallic title compound are grown by the Czochralski method from a stoichiometric mixture of the purified elements (W virtual seed, 4 mm/h).